Representation And Participation Of Women In Indonesian Political Parties - Pramudita, Roni Renaldi; Suyaman, Prahasti; Mulyanti, Asti Sri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
The role of women in Indonesia's political parties shows that women can take part in government regulatory decisions. However, women's representation in formal political institutions is still quite limited; the low representation is due to profound structural and cultural barriers. According to the Inter-Parliamentary Union, women's representation in Indonesia has never reached the target of 30% according to the provisions of Law number 2 of 2008 concerning political parties; even in the last five years, data shows that women's representation is only above 20%. This study specifically explores the role of patriarchal culture and the subordination of women in the political decision-making process as the leading causes. This study uses the normative juridical method by analysing data from legal literature sources and reviewing literature through transformative shorts to find the root cause of women's lack of representation in politics. The results of the study show that the lack of representation of women is due to a patriarchal culture created from the collective mindset of the community. The subordination of women in the political constellation is realised due to a lack of understanding from a managerial point of view and explicitly considers it difficult for women to make decisions because it always involves emotions. Thus, systematic efforts are needed through the SEP framework, Self-awareness, Education, Politics, and Promotion, to change public perceptions of the role of women, as well as reforms in political party structures and decision-making processes.